1997
DOI: 10.1136/vr.141.7.164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five tests for the detection of antibodies against chlamydial (enzootic) abortion of ewes

Abstract: Five tests for antibodies against chlamydial (enzootic) abortion of ewes were compared using 255 sera from experimentally (group 1) or naturally (group 2) infected animals, flocks free of the disease (group 3) and individual animals testing positively by the complement fixation test but from flocks with no evidence of chlamydial abortion (group 4). Sera from five specific pathogen-free lambs vaccinated with two different subtypes of Chlamydia pecorum were also included (group 5). All tests used some form of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
(19 reference statements)
3
21
1
2
Order By: Relevance
“…Although it has been reported that the CFT antibody titers are low in these apparently healthy sheep (31,37), in this study both the experimentally infected (group 3) and naturally infected (group 6) animals were found to be negative. This suggests that the lack of specificity of CFT in the field may be due to the arthritogenic and conjunctival subtypes rather than the more common enteric subtype, as suggested previously (19,22). CFT also performed better than has been reported by other groups, in which the sensitivity has been reported to be lower with either naturally or experimentally infected sheep (5,19,25), although six borderline positive samples and two negative samples were obtained from ewes that either aborted or lambed with heavily infected placentas (group 1A).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although it has been reported that the CFT antibody titers are low in these apparently healthy sheep (31,37), in this study both the experimentally infected (group 3) and naturally infected (group 6) animals were found to be negative. This suggests that the lack of specificity of CFT in the field may be due to the arthritogenic and conjunctival subtypes rather than the more common enteric subtype, as suggested previously (19,22). CFT also performed better than has been reported by other groups, in which the sensitivity has been reported to be lower with either naturally or experimentally infected sheep (5,19,25), although six borderline positive samples and two negative samples were obtained from ewes that either aborted or lambed with heavily infected placentas (group 1A).…”
Section: Discussionmentioning
confidence: 54%
“…This suggests that the lack of specificity of CFT in the field may be due to the arthritogenic and conjunctival subtypes rather than the more common enteric subtype, as suggested previously (19,22). CFT also performed better than has been reported by other groups, in which the sensitivity has been reported to be lower with either naturally or experimentally infected sheep (5,19,25), although six borderline positive samples and two negative samples were obtained from ewes that either aborted or lambed with heavily infected placentas (group 1A). The specificity of CFT and the variability of CFT antibody titers, in which very low or borderline titers are produced in some animals following abortion, reinforce the arguments that the test should be used only for flocks and not for the diagnosis of infection in individual animals (30).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It was shown that females with high antibody-titers against Salmonella underwent a decrease in their reproductive success, while antibody-titers against Chlamydophila and Coxiella were not related to the reproductive success of female chamois (Pioz et al, 2008b). The CFT used in the above mentioned studies is of inferior sensitivity and specificity and cross-reactivity to other species of the family Chlamydiaceae is well known (Markey et al, 1993;Donn et al, 1997;Jones et al, 1997;Rodolakis et al, 1998). Thus, false positive results due to cross-reaction with C.…”
Section: Salmonella Enterica Serovar Abortusovis Chlamydophila Abortmentioning
confidence: 99%
“…In the United Kingdom and elsewhere, the CFT is used by national veterinary laboratories to screen and accredit sheep and goats as being EAE free. However, the CFT can be insensitive and lacks specificity (20,26). In particular, antigenic cross-reactivity with C. pecorum, as well as with other gram-negative bacteria, such as Acinetobacter spp., complicates the interpretation of results.…”
mentioning
confidence: 99%